The role of inflammatory markers in COVID-19 associated rhino-orbital-cerebral mucormycosis patients - Chopra, Sunny; Kaur, Maninder; Bhagat, Sanjeev; Yadav, Vishav (International Journal of Research in Medical Sciences, 2023)
Background: India has experienced an unprecedented heave of mucormycosis (MCR) cases during second wave of COVID-19. Possible mechanisms may involve immune and inflammatory processes. The aim of the study is to estimate the role of inflammatory markers for triaging patients of COVID-19 associated rhino-orbital-cerebral mucormycosis (CAROCM) at tertiary care hospital in north India. Methods: A retrospective observational study was conducted between September 2021 to December 2021, at Government medical college and hospital, Patiala (Pb), 83 CAROCM patients admitted in ENT department were evaluated for serum ferritin, D-dimer and PCT. Results: The median age of the patients was 50 years. The number of male patients were 45 and female patients were 38. Based upon the medical history and associated comorbidities involved, 83 CAROCM patients were divided into three groups. 43 diabetic patients in group I, 33 patients with multiple risk factors in group II and 7 patients with no comorbidity in group III. The mean D-dimer levels were 702 ng/ml in group 1, 831ng/ml in group II and 399 ng/ml in group III, and ferritin levels were 522 ng/ml, 711 ng/ml and 426 ng/ml in group I, II and III respectively. Mean PCT levels in group I were 0.27 ng/ml, 1.32 ng/ml in group II and 0.42 ng/ml in group III. Conclusions: Our study concluded that a significant association was observed between levels of inflammatory markers and susceptibility factors. Serum ferritin, D-dimer and procalcitonin, can be used for assessing the severity of infection and decreases the mortality and morbidity in CAROCM patients.